Brucellosis in older person: a case report from Qatar - Hanadi Khamis Al Hamad (21406964) (2022)
Background Brucellosis is a multisystem disease with a broad spectrum of non-specific symptoms that generally occur within three weeks but sometimes up to 3 months after inoculation. Human brucellosis is quite uncommon in Elderly in Qatar. Case report This report describes a case of Brucellosis in acute geriatric unit under Rumailah Hospital in Qatar. The patient was an 81-year-old Qatari Gentle man, functionally able to walk with minimal assistance and had mild cognitive impairment who presented with high-grade fever with chills, anorexia, low back pain and arthralgia for 10 days. The above complaints occurred often for 1 month and had fever intermittently. Lab investigations revealed as high CRP 117 mg/l, low Hb 9.1 g/dl and mild elevation in ALP (151 µ/l) with normal leukocyte and platelet count. His blood culture positive for Brucella melitensis with high brucella Antibody titter 1:1280. The diagnosis made as Brucellosis. Discussion The clinical manifestations of Brucellosis are fever, night sweating, chills, arthralgia and loss of appetite. It seems pyrexia of unknown origin without other symptoms is most common presentation of Brucellosis in old age. The confirmation of Brucellosis made with serological tests, with significantly high titer, in the presence or absence of blood culture. Brucella antibody titers (≥1:160) are suggestive of active infection. Anemia and raised CRP and liver enzymes were the most prominent laboratory abnormalities in our patients. Previous study from Qatar reported that 41.7% had a history of raw milk consumption and 12.5% had a history of animal contact. The objectives of Brucellosis treatment include the prevention of complications and relapse. Conclusion Our case presented with classical symptoms and received appropriate treatment on time. However, atypical clinical presentation and lack of specific history taking can delay diagnosis and treatment; it leads to serious clinical disease progression with increased complications. From this case study, we would contribute to optimal assessment and to keep differential diagnosis for unknown cause of fever can be Brucellosis in geriatric population. Other Information Published in: The Aging Male License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/13685538.2022.2138851